A recycled wood composite engineered wood panel and its preparation process
Patent Information
- Application Number
- CN202611048750.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-09-01
AI Technical Summary
[0006]上述现有技术存在共同的技术问题:将脲醛残胶视为必须彻底清除的污染物,处理目标始终是最大化脱胶率;然而脱胶过程不可避免地损伤纤维形态和力学性能,且脱胶率越高纤维损伤程度越大,形成脱胶与保纤不可兼得的根本问题
1、本发明通过温和酸水解原位活化残胶氨基,将残胶从粘结障碍转化为粘结增强资源,无需追求高脱胶率即可实现优异胶合性能,从根本上解决了脱胶与保纤不可兼得的技术问题。
Abstract
Description
Technical Field
[0001] This invention relates to the field of wood composite materials technology, specifically to a recycled wood composite engineered wood panel and its preparation process. Background Technology
[0002] Urea-formaldehyde resin has become the most widely used adhesive in the wood-based panel industry due to its excellent processing performance and low production cost. With the increasing consumption of wood-based panels in my country's furniture and building decoration industries, a large amount of wood-based panels and their products are discarded and scrapped each year. Utilizing waste wood-based panels to produce recycled wood-based panels is an important way to alleviate the supply and demand imbalance of timber raw materials and achieve sustainable development of the timber industry.
[0003] However, the residual cured urea-formaldehyde resin in waste engineered wood products limits the performance of recycled engineered wood products; existing technologies mainly remove residual resin through methods such as hydrothermal treatment, acid hydrolysis, or steam explosion. For example, hydrothermal treatment of waste fiberboard at 120°C for 60 minutes with hydrochloric acid can reduce the total nitrogen content by 87.81%, but the mass loss reaches 54.51%.
[0004] Hydrolysis with oxalic acid at 122℃ for 30 to 60 minutes can remove 90% of the nitrogen content, but the mechanical properties of the treated fibers deteriorate. Existing patent CN103740324A discloses a formaldehyde-free adhesive using tannin-glyoxal resin as a crosslinking reinforcing agent, but its application in log fiberboard systems does not address the disposal of residual adhesive in regenerated fibers.
[0005] Existing patent CN119331188A discloses a method for preparing urea-formaldehyde resin by depolymerization of urea-formaldehyde waste glue, but this technology is geared towards the recycling of liquid waste glue in the glue-making process and does not involve the treatment of residual glue that has been solidified on the fiber surface.
[0006] The aforementioned existing technologies share a common technical problem: they treat urea-formaldehyde residue as a pollutant that must be completely removed, and the treatment goal is always to maximize the degumming rate; however, the degumming process inevitably damages the fiber morphology and mechanical properties, and the higher the degumming rate, the greater the degree of fiber damage, forming a fundamental problem that degumming and fiber preservation cannot be achieved simultaneously.
[0007] Meanwhile, when existing formaldehyde-free adhesive systems are applied to recycled fibers, residual adhesive prevents direct contact between the adhesive and the fiber surface, resulting in lower bonding strength compared to virgin wood fiber systems. Therefore, there is an urgent need for a new type of recycled wood composite board technology that can overcome the aforementioned technical biases and transform residual adhesive from a bonding barrier into a bonding enhancement resource. Summary of the Invention
[0008] The primary objective of this invention is to provide a recycled wood composite engineered wood panel and its preparation process.
[0009] A further objective of this invention is to provide a recycled wood composite board, comprising recycled wood fibers pretreated with mild acid hydrolysis and a coordination adhesive system. The recycled wood fibers are derived from waste urea-formaldehyde resin-bonded engineered wood products and are treated with an organic acid buffer solution with a pH of 3.5 to 5.0 at 80 to 120°C for 15 to 30 minutes. Residual urea-formaldehyde resin fragments on the fiber surface partially depolymerize and generate amino groups in situ. The amino content on the fiber surface is 2.0 to 5.0 μmol / g. The coordination adhesive system contains polyphenolic compounds and trivalent metal ions. The polyphenolic compounds and trivalent metal ions form a coordination crosslinking network, and the amino groups on the fiber surface coordinate with the trivalent metal ions to form a polyphenolic compound-metal-amino dual coordination crosslinking network.
[0010] Preferably, based on 100 parts of oven-dried regenerated wood fiber, the amount of polyphenol compound added is 5 to 8 parts, and the molar ratio of trivalent metal ions to polyphenol compound is 0.8 to 1.5.
[0011] Preferably, the polyphenol compound is tannic acid with a molecular weight of 1701 g / mol and a galloyl group number of not less than 10, and the trivalent metal ion is ferric ion.
[0012] Preferably, the organic acid buffer solution is a citric acid-sodium citrate buffer solution with a concentration of 0.02 to 0.10 mol / L.
[0013] Preferably, the board has a three-layer gradient density structure, with the top and bottom layers using fine recycled wood fibers with a length of 0.3 to 1.0 mm, and the core layer using coarse recycled wood fibers with a length of 1.0 to 3.0 mm. The board density is 0.75 to 0.85 g / cm³. 3 .
[0014] A process for preparing the aforementioned recycled wood composite engineered wood panel includes the following steps: Step 1: Crush and separate waste urea-formaldehyde resin-bonded engineered wood panels into recycled wood fibers; Step 2: Immerse the regenerated wood fiber in an organic acid buffer solution with a pH of 3.5 to 5.0 and treat it at 80 to 120°C for 15 to 30 minutes with a solid-liquid ratio of 1:8 to 1:12, so that the residual urea-formaldehyde resin fragments on the fiber surface partially depolymerize and generate amino groups in situ. Step 3: After washing and drying, apply polyphenol compound aqueous solution and trivalent metal salt aqueous solution in sequence; Step 4: After laying and molding, hot press at a temperature of 180 to 200°C, a pressure of 3.0 to 4.0 MPa, and a time of 5 to 7 minutes.
[0015] Preferably, in step two, the organic acid buffer solution is a citric acid-sodium citrate buffer solution with a concentration of 0.02 to 0.10 mol / L, the treatment temperature is 90 to 105°C, and the treatment time is 18 to 25 min.
[0016] Preferably, in step three, the polyphenol compound is tannic acid, the trivalent metal salt is ferric chloride hexahydrate, the mass fraction of the tannic acid aqueous solution is 15% to 25%, the mass fraction of the ferric chloride aqueous solution is 10% to 25%, the amount of tannic acid added is 5% to 8% of the dry fiber mass, and the molar ratio of trivalent iron ions to tannic acid is 0.8 to 1.5.
[0017] Preferably, in step four, the hot-pressing temperature is 185 to 195°C, the pressure is 3.2 to 3.8 MPa, the time is 5.5 to 6.5 min, and the target density of the board is 0.78 to 0.84 g / cm³. 3 .
[0018] Preferably, the method further includes a recycling step in which the waste board is immersed in an aqueous solution of citric acid with a pH of 3.0 to 3.5 and treated at 50 to 70°C for 2 to 4 hours to dissociate the coordination crosslinking network, separate and recycle the regenerated wood fibers, and then the recycled fibers are re-hot-pressed after being gently acid-hydrolyzed again and sizing with a coordination adhesive to prepare new boards.
[0019] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention activates residual adhesive amino groups in situ through mild acid hydrolysis, transforming residual adhesive from an adhesive barrier into an adhesive enhancement resource. It achieves excellent bonding performance without pursuing a high degumming rate, fundamentally solving the technical problem that degumming and fiber retention cannot be achieved simultaneously.
[0020] 2. The tannic acid-iron-amino dual coordination crosslinking network constructed in this invention improves the mechanical properties of regenerated fiber engineered wood panels, with static bending strength reaching 31 to 37 MPa and internal bonding strength reaching 0.65 to 0.82 MPa.
[0021] 3. The adhesive system used in this invention is completely formaldehyde-free, with a formaldehyde release of less than 0.3 mg / L, thus eliminating the formaldehyde pollution problem of recycled engineered wood products at the source.
[0022] 4. The coordination crosslinking network of the present invention has pH-responsive reversibility. After the board reaches the end of its service life, the coordination bonds can be dissociated and the fibers can be recovered by soaking in a weak acid. The recovered fibers can be reused to prepare new boards. The fiber recovery rate is over 85%, realizing the closed-loop recycling of recycled wood composite artificial boards.
[0023] 5. The mild acid hydrolysis conditions of this invention are mild and easy to operate. The citric acid, tannic acid and ferric chloride used are all inexpensive and readily available chemical raw materials. The preparation process is compatible with existing artificial board production lines and has prospects for industrial application. Detailed Implementation
[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] The core mechanism of this invention lies in reconstructing the cured urea-formaldehyde resin remaining on the surface of waste engineered wood fiber from an adhesion barrier into a potential reaction resource.
[0026] The crosslinked network of cured urea-formaldehyde resin contains a large number of methylene bridges. Under mild acidic conditions, i.e., pH 3.5 to 5.0 and temperature 80 to 120°C, the methylene bridges selectively break, generating amino-terminated fragments.
[0027] This process is the reverse of the urea-formaldehyde resin curing reaction, but under mild conditions, only partial depolymerization occurs instead of complete degradation, resulting in the in-situ formation of dense primary and secondary amino groups on the fiber surface.
[0028] After mild acid hydrolysis, the nitrogen on the fiber surface changes from a methylene bridged form to an amino form, and the surface amino content increases from about 0.5 μmol / g before treatment to 2.0 to 5.0 μmol / g.
[0029] The coordination bonding between the generated amino groups and ferric ions is the key unconventional mechanism of this invention.
[0030] In coordination chemistry, the lone pair of electrons of the nitrogen atom in an amino group can donate electron pairs to the empty d orbitals of a ferric ion to form a coordinate bond. This invention utilizes this principle, enabling the amino groups generated in situ on the fiber surface to participate in the construction of the coordination network of ferric ions together with tannic acid, forming a tannic acid-iron-amino dual-coordinate cross-linked network.
[0031] Specifically, trivalent iron ions form coordination bonds with pyrogallol and catechol groups in tannic acid molecules (iron-tannic acid coordination) and with amino groups on the fiber surface (iron-amino coordination). This dual coordination network solidifies during hot pressing, giving the board high strength and high water resistance. Other trivalent metal ions such as Al... 3+ Similarly, empty d orbitals can form coordination bonds with tannic acid phenolic hydroxyl groups and amino groups on the fiber surface to construct similar dual-coordinate cross-linking networks; other polyphenolic compounds containing catechol or pyrogallol structures can also form similar coordination cross-linking structures with trivalent metal ions.
[0032] This mechanism is manifested in the following aspects: By reconstructing urea-formaldehyde residue from a pollutant that needs to be removed into an activatable reaction resource, this overturns the long-standing technological bias in the field. The coordination bonding of amino groups with ferric ions is not a known bonding method in the field of wood composites. Existing metal-polyphenol coordination bonding systems only utilize the coordination between polyphenols and metals, without involving the participation of amino groups on the fiber surface in the coordination network. In the dual coordination network, the iron-tannic acid coordination and the iron-amino coordination do not exist independently and in parallel, but rather share ferric ion nodes to form a cross-linked interpenetrating structure. This makes the amino groups on the fiber surface a bridge connecting the inorganic metal coordination centers and the organic wood fiber matrix, fundamentally changing the bonding mode of the adhesive interface.
[0033] The critical effect of the mild acid hydrolysis parameter window is key to the success of this invention. When the hydrolysis conditions are too mild, i.e., pH above 5.0 or temperature below 80°C, the methylene bridge bonds in the urea-formaldehyde resin are not sufficiently broken, resulting in insufficient amino group formation on the fiber surface and a limited number of iron-amino coordination bonds, leading to board performance similar to untreated regenerated fibers. When the hydrolysis conditions are too severe, i.e., pH below 3.5 or temperature above 120°C, the urea-formaldehyde resin is excessively depolymerized, resulting in the hydrolysis and dissolution of a large amount of hemicellulose, a decrease in the degree of cellulose polymerization, and a deterioration in the fiber's mechanical properties. Even with sufficient amino group formation, the performance loss caused by fiber damage cannot be compensated. Only within the critical window of pH 3.5 to 5.0, temperature 80 to 120°C, and time 15 to 30 minutes can sufficient amino group formation and fiber quality maintenance be achieved simultaneously. This window cannot be obtained without inventive effort.
[0034] The reversibility of the coordination cross-linking network enables the board to be recycled. The iron-tannic acid and iron-amino coordination bonds can dissociate under weakly acidic conditions, i.e., pH 3.0 to 3.5. By immersing waste boards in a citric acid aqueous solution with a pH of 3.0 to 3.5 at 50 to 70°C for 2 to 4 hours, the dual coordination network gradually dissociates, the fibers separate, and the recovered fibers can be recycled into new boards after gentle acid hydrolysis and application of coordination adhesives, thus achieving a closed-loop recycling of recycled wood-based composite panels.
[0035] Raw material source: Waste medium-density fiberboard: 12mm thick, urea-formaldehyde resin bonded, poplar fiber, density 0.75 g / cm³ 3 It comes from scrap materials produced by a furniture factory.
[0036] Citric acid monohydrate: analytical grade, purity not less than 99.5%, molecular weight 210.14 g / mol, Sinopharm Chemical Reagent Co., Ltd.
[0037] Trisodium citrate dihydrate: analytical grade, purity not less than 99.0%, molecular weight 294.10 g / mol, Sinopharm Chemical Reagent Co., Ltd.
[0038] Tannic acid: analytical grade, molecular weight 1701 g / mol, number of galloyl units not less than 10, content not less than 95%, Shanghai Maclean Biochemical Technology Co., Ltd.
[0039] Ferric chloride hexahydrate: analytical grade, purity not less than 98.0%, molecular weight 270.30 g / mol, Sinopharm Chemical Reagent Co., Ltd.
[0040] Aluminum trichloride hexahydrate: analytical grade, purity not less than 97.0%, molecular weight 241.43 g / mol, Sinopharm Chemical Reagent Co., Ltd.
[0041] Glacial acetic acid: analytical grade, purity not less than 99.5%, molecular weight 60.05 g / mol, Sinopharm Chemical Reagent Co., Ltd.
[0042] Disodium ethylenediaminetetraacetate: analytical grade, purity not less than 99.0%, Sinopharm Chemical Reagent Co., Ltd.
[0043] Oxalic acid dihydrate: analytical grade, purity not less than 99.5%, molecular weight 126.07 g / mol, Sinopharm Chemical Reagent Co., Ltd.
[0044] Hydrochloric acid: analytical grade, mass fraction 36% to 38%, Sinopharm Chemical Reagent Co., Ltd.
[0045] Sodium hydroxide: analytical grade, purity not less than 96%, Sinopharm Chemical Reagent Co., Ltd.
[0046] Sodium chlorite: analytical grade, purity not less than 80%, Sinopharm Chemical Reagent Co., Ltd.
[0047] Sodium chloride: analytical grade, purity not less than 99.5%, molecular weight 58.44 g / mol, Sinopharm Chemical Reagent Co., Ltd.
[0048] Polymethylene polyphenyl isocyanate: Wannate PM-200, NCO mass fraction 30.5%, viscosity 200 mPa·s, Wanhua Chemical Group Co., Ltd.
[0049] Urea-formaldehyde resin adhesive: F / U molar ratio 1.05, solid content 52%, viscosity 45 mPa·s, curing agent is 20% ammonium chloride aqueous solution, Guangxi Fenglin Wood Industry Group Co., Ltd.
[0050] Paraffin emulsion: 50% solids content, pH 7 to 8, Shanghai Yigong Wax Products Co., Ltd. Example
[0051] Raw material formula: 100g of waste medium-density fiberboard, based on oven-dry fiber; 1000mL of citric acid-sodium citrate buffer solution, concentration 0.05 mol / L, pH 4.0; 6.0g of tannic acid; 1.0g of ferric chloride hexahydrate; 1.0g of paraffin emulsion, based on solids 0.5g.
[0052] Preparation process: Step 1: Cut the waste medium-density fiberboard into 50mm×50mm pieces, and crush them into recycled wood fibers using a hammer mill. The screen of the mill has a 5mm aperture, and the fine powder is removed by passing it through a 0.3mm square hole screen. The resulting recycled wood fibers have a length of 0.3 to 3.0mm and a width of 0.02 to 0.10mm.
[0053] Step 2: Impregnate the regenerated wood fiber in a 0.05 mol / L citric acid-sodium citrate buffer solution at pH 4.0 with a solid-liquid ratio of 1:10. Heat the solution to 100°C in a sealed stainless steel reactor, hold it at that temperature for 20 min, stir at a rate of 100 r / min, and then cool it to room temperature.
[0054] Step 3: Drain the hydrolysate, wash the fibers three times with 500 mL of deionized water each time, dehydrate by vacuum filtration at a vacuum degree of 0.08 MPa, and dry in a forced-air drying oven at 80℃ to a moisture content of 5.0%. Dissolve 6.0 g of tannic acid in 18 g of deionized water to prepare a 25% tannic acid aqueous solution, and spray it evenly onto the dried fiber surface, stirring for 5 min at a stirring speed of 60 r / min. Dissolve 1.0 g of ferric chloride hexahydrate in 4 g of deionized water to prepare a 20% ferric chloride aqueous solution, and spray it evenly onto the fiber surface, stirring for 5 min. Add 1.0 g of paraffin emulsion and stir for 3 min. Dry the sizing fibers in a 60℃ ventilated drying oven to a moisture content of 10%.
[0055] Step 4: Lay the sizing-treated fibers in a three-layer structure: the top and bottom layers each use 30% fine fibers (0.3 to 1.0 mm in length), and the core layer uses 40% coarse fibers (1.0 to 3.0 mm in length). The laying area is 400 mm × 400 mm. Pre-compression pressure is 1.0 MPa for 30 seconds. Hot-compression temperature is 190℃, pressure is 3.5 MPa, and time is 6 minutes, with a target density of 0.82 g / cm³. 3 The target thickness is 12mm. After hot pressing, the material is cooled to room temperature for 24 hours, then equilibrated at 20℃ and 65% relative humidity for 48 hours, and finally trimmed to 380mm×380mm. Example
[0056] Raw material formula: 100g of waste medium-density fiberboard, based on oven-dry fiber; 1000mL of citric acid-sodium citrate buffer solution, concentration 0.05 mol / L, pH 3.5; 6.0g of tannic acid; 1.2g of ferric chloride hexahydrate; 1.0g of paraffin emulsion, based on solids 0.5g.
[0057] Preparation process: Step one is the same as in Example 1.
[0058] Step 2: The hydrolysis conditions are pH 3.5, temperature 110℃, and time 15 min, with the remaining parameters being the same as in Example 1.
[0059] Step 3: Prepare a 20% (w / w) aqueous solution of 1.2g of ferric chloride hexahydrate and spray it. The rest is the same as in Example 1. Step 4 is the same as in Example 1. Example
[0060] Raw material formula: 100g of waste medium-density fiberboard, based on oven-dry fiber; 1000mL of citric acid-sodium citrate buffer solution, concentration 0.05 mol / L, pH 5.0; 6.0g of tannic acid; 0.8g of ferric chloride hexahydrate; 1.0g of paraffin emulsion, based on solids 0.5g.
[0061] Preparation process: Step one is the same as in Example 1.
[0062] Step 2: The hydrolysis conditions are pH 5.0, temperature 85℃, and time 30 min, with the remaining parameters being the same as in Example 1.
[0063] Step 3: Prepare a 20% (w / w) aqueous solution of 0.8g of ferric chloride hexahydrate for spraying; the rest is the same as in Example 1. Step 4 is the same as in Example 1. Example
[0064] Raw material formula: 100g of waste medium-density fiberboard, based on oven-dry fiber; 1000mL of acetate-sodium acetate buffer solution, concentration 0.05mol / L, pH 4.0; 6.0g of tannic acid; 1.0g of ferric chloride hexahydrate; 1.0g of paraffin emulsion, based on solids 0.5g.
[0065] Preparation process: Step one is the same as in Example 1.
[0066] Step 2: Acetic acid-sodium acetate buffer solution was used instead of citric acid-sodium citrate buffer solution. The pH was 4.0, the temperature was 100℃, and the time was 20 min. The other parameters were the same as in Example 1.
[0067] Steps three and four are the same as in Example 1. Example
[0068] Raw material formula: 100g of waste medium-density fiberboard, based on oven-dry fiber; 1000mL of citric acid-sodium citrate buffer solution, concentration 0.05 mol / L, pH 4.0; 6.0g of tannic acid; 0.9g of aluminum trichloride hexahydrate; 1.0g of paraffin emulsion, based on solids 0.5g.
[0069] Preparation process: Step one is the same as in Example 1. Step two is the same as in Example 1.
[0070] Step 3: Replace ferric chloride hexahydrate with 0.9g of aluminum trichloride hexahydrate and prepare a 20% aqueous solution for spraying. The rest is the same as in Example 1.
[0071] Step four is the same as in Example 1.
[0072] Comparative Example 1: Raw material formula: 100g of waste medium-density fiberboard, calculated as oven-dry fiber; 6.0g of tannic acid; 1.0g of ferric chloride hexahydrate; 1.0g of paraffin emulsion, calculated as solids.
[0073] Preparation process: Step one is the same as in Example 1.
[0074] The mild acid hydrolysis pretreatment in step two is omitted.
[0075] Unhydrolyzed regenerated wood fibers were directly dried to a moisture content of 5.0%, and then sizing and hot-pressed according to steps three and four of Example 1.
[0076] Comparative Example 2: Raw material formula: 100g of waste medium-density fiberboard (calculated as oven-dry fiber); 1000mL of hydrochloric acid aqueous solution, concentration 0.10 mol / L, pH 2.0; 6.0g of tannic acid; 1.0g of ferric chloride hexahydrate; 1.0g of paraffin emulsion (calculated as solids).
[0077] Preparation process: Step one is the same as in Example 1.
[0078] Step 2: Use 0.10 mol / L hydrochloric acid aqueous solution as hydrolysis solution, pH 2.0, temperature 130℃, time 45 min, solid-liquid ratio 1:10, and other parameters are the same as in Example 1.
[0079] Steps three and four are the same as in Example 1.
[0080] Comparative Example 3: Raw material formula: 100g of waste medium-density fiberboard (calculated as oven-dry fiber); 1000mL of citric acid-sodium citrate buffer solution (concentration 0.05 mol / L, pH 4.0); 6.0g of tannic acid; 0.3g of ferric chloride hexahydrate; 1.0g of paraffin emulsion (calculated as solids).
[0081] Preparation process: Step one is the same as in Example 1.
[0082] Step two is the same as in Example 1.
[0083] Step 3: Use 0.3g of ferric chloride hexahydrate, with a molar ratio of ferric ions to tannic acid of 0.3, to prepare a 20% (w / w) aqueous solution for spraying. The rest is the same as in Example 1.
[0084] Step four is the same as in Example 1.
[0085] Comparative Example 4: Raw material formula: 100g of waste medium-density fiberboard (MDF), calculated as oven-dry fiber; 8.0g of urea-formaldehyde resin adhesive, calculated as solids; 0.4g of ammonium chloride curing agent; 1.0g of paraffin emulsion, calculated as solids.
[0086] Preparation process: Step one is the same as in Example 1.
[0087] The mild acid hydrolysis pretreatment in step two is omitted. Unhydrolyzed regenerated wood fibers are directly dried to a moisture content of 5.0%. 8.0 g of urea-formaldehyde resin adhesive and 2.0 g of 20% ammonium chloride aqueous solution are applied and stirred for 5 minutes. 1.0 g of paraffin emulsion is then added and stirred for 3 minutes. Step four is the same as in Example 1, with a hot-pressing temperature of 180°C.
[0088] Comparative Example 5: Raw material formula: 100g of fresh poplar fiber, on an oven-dry basis; 6.0g of tannic acid; 1.0g of ferric chloride hexahydrate; 1.0g of paraffin emulsion, on a solid basis, 0.5g.
[0089] Preparation process: The fiber is made from fresh poplar wood chips through a hot mill, with a fiber length of 1.0 to 5.0 mm and a width of 0.02 to 0.15 mm, and contains no urea-formaldehyde resin residue.
[0090] The mild acid hydrolysis pretreatment step was omitted. The fresh fibers were dried to a moisture content of 5.0%, and sizing and hot pressing were performed according to steps three and four of Example 1.
[0091] Comparative Example 6: Raw material formula: 100g of waste medium-density fiberboard (calculated as oven-dry fiber); 4.0g of sodium chlorite; 2.0mL of glacial acetic acid; 6.0g of tannic acid; 0.2g of sodium chloride; 1.0g of paraffin emulsion (calculated as solids).
[0092] Preparation process: Step one is the same as in Example 1.
[0093] Step 2, using oxidative pretreatment instead of mild acid hydrolysis: the regenerated wood fiber is impregnated in a 1000mL aqueous solution containing 4.0g sodium chlorite and 2.0mL glacial acetic acid, treated at 80℃ for 2h, and then washed and dried.
[0094] Step 3: Dissolve 6.0g of tannic acid in 54g of deionized water and spray; dissolve 0.2g of sodium chloride in 50g of deionized water and spray; the molar ratio of sodium ions to tannic acid is 1.0; the rest is the same as in Example 1.
[0095] Step four is the same as in Example 1.
[0096] Comparative Example 7: Raw material formula: 100g of waste medium-density fiberboard, based on oven-dry fiber; 1000mL of citric acid-sodium citrate buffer solution, concentration 0.05 mol / L, pH 4.0; 5.0g of polymethylene polyphenyl isocyanate; 1.0g of paraffin emulsion, based on solids 0.5g.
[0097] Preparation process: Step one is the same as in Example 1.
[0098] Step two is the same as in Example 1, that is, the same mild acid hydrolysis pretreatment conditions are used.
[0099] Step 3: Replace tannic acid and ferric chloride with 5.0g of polymethylene polyphenyl isocyanate, spray it evenly onto the fiber surface, stir and mix for 5 minutes, and the rest is the same as in Example 1.
[0100] Step four is the same as in Example 1.
[0101] Test method: The static bending strength and modulus of elasticity shall be performed in accordance with the provisions of 4.7 in GB / T 17657-2013. The universal testing machine model is CMT5504, the loading rate is 5 mm / min, the span is 256 mm, the specimen size is 380 mm × 50 mm × 12 mm, and the average value of 6 specimens in each group shall be taken.
[0102] The internal bond strength shall be performed in accordance with the provisions of 4.8 in GB / T 17657-2013. The universal testing machine model is CMT5504, the loading rate is 2 mm / min, the specimen size is 50mm×50mm×12mm, and the average value of 6 specimens in each group shall be taken.
[0103] The 24-hour water absorption thickness expansion rate shall be performed in accordance with the provisions of 4.5 in GB / T 17657-2013, with a water temperature of 20±2℃, an immersion time of 24 hours, and a specimen size of 50mm×50mm×12mm. The average value of 6 specimens in each group shall be taken.
[0104] Formaldehyde emission was measured according to the desiccator method specified in GB / T 17657-2013, section 4.60. The specimen size was 150mm×50mm×12mm, and the average value of 3 specimens in each group was taken.
[0105] The amino content on the fiber surface was determined by potentiometric titration: 1.0 g of oven-dried fiber was suspended in 50 mL of 0.01 mol / L hydrochloric acid solution, and titrated to pH 7.0 with 0.01 mol / L sodium hydroxide standard solution. A blank sample was used as a control. The amino content was calculated based on the amount of hydrochloric acid consumed. The average value was taken from three tests for each group. The total nitrogen content of the fiber was determined according to the Kjeldahl method specified in GB / T 29857-2013, using a Kjeltec 8400 instrument. The average value was taken for each group of three tests.
[0106] Fiber recovery rate test method: The board is immersed in a 0.05 mol / L citric acid aqueous solution with pH 3.2, the liquid-to-solid ratio is 20:1, and the board is treated at a constant temperature of 60℃ with shaking for 3 hours at a shaking frequency of 100 times / min. The fiber is collected by vacuum filtration, washed, dried and weighed. The ratio of the mass of recovered fiber to the mass of original fiber is the fiber recovery rate.
[0107] Test results: Table 1. Test Results of Mechanical Properties and Formaldehyde Emission of Recycled Wood Composite Panels Example 1 36.5 3690 0.82 10.8 0.22 Example 2 33.7 3490 0.74 11.5 0.18 Example 3 31.2 3220 0.65 13.2 0.28 Example 4 34.8 3520 0.78 11.2 0.20 Example 5 32.6 3370 0.71 12.4 0.21 Comparative Example 1 16.5 1870 0.28 21.2 0.75 Comparative Example 2 14.2 1680 0.19 25.6 0.06 Comparative Example 3 22.8 2480 0.42 17.3 0.25 Comparative Example 4 21.5 2340 0.35 17.8 1.35 Comparative Example 5 46.8 4820 1.52 8.8 0.02 Comparative Example 6 19.3 2150 0.33 19.5 0.68 Comparative Example 7 27.5 2850 0.55 13.8 0.18 Test methods: Static bending strength and modulus of elasticity were determined according to 4.7 of GB / T 17657-2013; internal bond strength was determined according to 4.8 of GB / T 17657-2013; 24h water absorption thickness swelling rate was determined according to 4.5 of GB / T 17657-2013; and formaldehyde emission was determined according to the desiccator method in 4.60 of GB / T 17657-2013.
[0108] Results analysis: The static bending strength of Examples 1 to 5 was 31.2 to 36.5 MPa, the elastic modulus was 3220 to 3690 MPa, the internal bond strength was 0.65 to 0.82 MPa, the 24-hour water absorption thickness swelling rate was 10.8 to 13.2%, and the formaldehyde release was 0.18 to 0.28 mg / L.
[0109] Comparative Example 1, without mild acid hydrolysis pretreatment, had a static bending strength of 16.5 MPa and an internal bond strength of 0.28 MPa. Residual urea-formaldehyde resin on the fiber surface blocked the interfacial bonding of the tannic acid-iron coordination adhesive.
[0110] Comparative Example 2 underwent severe acid hydrolysis, resulting in a formaldehyde release of 0.06 mg / L, a static bending strength of 14.2 MPa, an internal bond strength of 0.19 MPa, and a 24-hour water absorption thickness swelling rate of 25.6%. The severe hydrolysis caused fiber damage and hemicellulose dissolution.
[0111] Example 1 showed a static bending strength of 36.5 MPa, Comparative Example 1 showed 16.5 MPa, and Comparative Example 2 showed 14.2 MPa. Mild acid hydrolysis treatment within the critical window increased the static bending strength by more than 20.0 MPa, demonstrating the nonlinear effect of the critical window of hydrolysis parameters.
[0112] In Comparative Example 3, the molar ratio of ferric ions to tannic acid was 0.3, which is lower than the critical window limit of 0.8. The coordination crosslinking density was insufficient, and the static bending strength was 22.8 MPa. The coordination crosslinking density has a critical threshold for the performance of the board.
[0113] Comparative Example 4 used a traditional urea-formaldehyde resin adhesive, with a formaldehyde release of 1.35 mg / L, exceeding the E0 limit.
[0114] Comparative Example 5 uses fresh poplar fiber, with a static bending strength of 46.8 MPa and an internal bond strength of 1.52 MPa, serving as a performance reference for the original wood fiber system. The static bending strength of Example 1 is 78% of that of Comparative Example 5.
[0115] Comparative Example 6 uses an oxidation pretreatment and a sodium ion-tannic acid supramolecular system. The static bending strength is 19.3 MPa and the internal bond strength is 0.33 MPa. The carboxyl groups generated on the surface of fresh fibers by the oxidation pretreatment can enhance the electrostatic effect of sodium ions, but the urea-formaldehyde residue in the regenerated fibers prevents the effective contact between the adhesive and the fiber matrix.
[0116] Comparative Example 7 was pretreated with mild acid hydrolysis and then subjected to polymethylene polyphenyl isocyanate. The static bending strength was 27.5 MPa and the internal bond strength was 0.55 MPa. The amino groups reacted with the isocyanate groups to form urea bonds to enhance the bonding. However, this reaction was limited to local point bonding on the fiber surface and could not form a three-dimensional cross-linked interpenetrating structure of tannic acid-iron-amino dual coordination network.
[0117] Table 2. Test results of amino content and total nitrogen content on fiber surface: Untreated recycled fibers none 3.48 0.52 Example 1 Fiber pH 4.0, 100℃, 20 min 2.76 3.54 Example 2 Fiber pH 3.5, 110℃, 15min 2.43 3.12 Example 3 Fiber pH 5.0, 85℃, 30 min 3.05 2.18 Comparative Example 2 Fiber pH 2.0, 130℃, 45 min 0.82 0.31 Comparative Example 5: Fiber, i.e., fresh fiber none 0.08 0.06 Test methods: Total nitrogen content was determined by the Kjeldahl method according to GB / T 29857-2013, and surface amino content was determined by potentiometric titration.
[0118] Results Analysis: In Example 1, after mild acid hydrolysis, the total nitrogen content of the fiber decreased from 3.48% to 2.76%, while the surface amino content increased from 0.52 μmol / g to 3.54 μmol / g, an increase of 580%. This data confirms that mild acid hydrolysis partially depolymerizes urea-formaldehyde resin fragments on the fiber surface, breaks methylene bridge bonds to generate amino-terminated fragments, and exposes amino groups on the fiber surface.
[0119] In Example 2, the fiber was hydrolyzed at a higher temperature and lower pH, resulting in a decrease in total nitrogen content to 2.43% and a surface amino content of 3.12 μmol / g. The increased hydrolysis intensity led to further degradation and dissolution of some amino fragments.
[0120] In Example 3, the fiber was hydrolyzed under relatively mild conditions, with a total nitrogen content of 3.05% and a surface amino content of 2.18 μmol / g. The hydrolysis was incomplete, and the methylene bridge bonds were not fully broken.
[0121] In Comparative Example 2, the fiber was hydrolyzed under severe conditions, and the total nitrogen content decreased to 0.82%, the surface amino content was 0.31 μmol / g, the urea-formaldehyde resin was excessively depolymerized, a large amount of nitrogen-containing fragments were dissolved, and very few amino groups remained on the fiber surface.
[0122] The data revealed the critical window effect of hydrolysis parameters: if hydrolysis is too weak, insufficient amino group formation will occur; if hydrolysis is too strong, nitrogen-containing fragments will dissolve and the fibers will be damaged. Only within the critical window of pH 3.5 to 5.0, 80 to 120℃, and 15 to 30 min can the surface amino content reach an effective level of more than 2.0 μmol / g.
[0123] Table 3. Results of recycling performance test in Example 1: 1st time 36.5 3690 0.82 10.8 92.3 2nd time 31.4 3160 0.68 13.3 89.1 3rd time 26.8 2650 0.51 16.5 85.4 Test method: In each cycle, the board was immersed in a 0.05 mol / L citric acid aqueous solution at pH 3.2 and treated at 60℃ for 3h. After separating and recovering the fibers, the board was re-prepared according to the process in Example 1. The static bending strength and modulus of elasticity were determined according to 4.7 of GB / T 17657-2013, the internal bond strength was determined according to 4.8, and the 24h water absorption thickness swelling rate was determined according to 4.5.
[0124] Results Analysis: In Example 1, the static bending strength of the board was 36.5 MPa in the first cycle, decreased to 31.4 MPa in the second cycle (86% retention rate), and decreased to 26.8 MPa in the third cycle (73% retention rate). The internal bond strength decreased sequentially from 0.82 MPa to 0.68 MPa and 0.51 MPa. The fiber recovery rate decreased sequentially from 92.3% to 89.1% and 85.4%, but remained above 85% after three cycles.
[0125] The reason for the gradual decline in performance is that the mild acid hydrolysis and recycling process in each cycle leads to further shortening of fiber length, cumulative loss of hemicellulose, and gradual consumption of urea-formaldehyde resin fragments after multiple hydrolysis cycles, resulting in a gradual decrease in surface amino content.
[0126] However, even after the third cycle, the static bending strength of 26.8 MPa and the internal bond strength of 0.51 MPa still exceed the requirements of 25 MPa and 0.45 MPa for P6 type particleboard in GB / T 4897-2015, respectively, indicating that the reversibility of the coordination crosslinking network of the present invention gives the board a practical recycling capability.
[0127] Traditional urea-formaldehyde resin bonded recycled engineered wood panels suffer from irreversible curing of the adhesive layer after the end of their lifespan, making it impossible to effectively separate and recycle the fibers. This invention solves this technical problem through a pH-responsive reversible coordination bond design.
[0128] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention.
Claims
1. A recycled wood composite engineered wood panel, characterized in that: The invention comprises regenerated wood fibers pretreated with mild acid hydrolysis and a coordination adhesive system. The regenerated wood fibers are derived from waste urea-formaldehyde resin-plywood. They are treated with an organic acid buffer solution with a pH of 3.5 to 5.0 at 80 to 120°C for 15 to 30 minutes. The residual urea-formaldehyde resin fragments on the fiber surface partially depolymerize and generate amino groups in situ. The amino content on the fiber surface is 2.0 to 5.0 μmol / g. The coordination adhesive system contains polyphenolic compounds and trivalent metal ions. The polyphenolic compounds and trivalent metal ions form a coordination crosslinking network, and the amino groups on the fiber surface coordinate with the trivalent metal ions to form a polyphenolic compound-metal-amino dual coordination crosslinking network.
2. The recycled wood composite engineered wood panel as described in claim 1, characterized in that: Based on 100 parts of oven-dried regenerated wood fiber, the amount of polyphenol compound added is 5 to 8 parts, and the molar ratio of trivalent metal ions to polyphenol compound is 0.8 to 1.
5.
3. The recycled wood composite engineered wood panel as described in claim 1, characterized in that: The polyphenol compound is tannic acid with a molecular weight of 1701 g / mol and a galloyl group number of not less than 10. The trivalent metal ion is ferric ion.
4. The recycled wood composite engineered wood panel as described in claim 1, characterized in that: The organic acid buffer solution is a citric acid-sodium citrate buffer solution with a concentration of 0.02 to 0.10 mol / L.
5. The recycled wood composite engineered wood panel as described in claim 1, characterized in that: It has a three-layer gradient density structure. The top and bottom layers use fine recycled wood fibers with a length of 0.3 to 1.0 mm, while the core layer uses coarse recycled wood fibers with a length of 1.0 to 3.0 mm. The board density is 0.75 to 0.85 g / cm³. 3 .
6. A preparation process for a recycled wood composite engineered wood panel as described in claim 1, characterized in that, Includes the following steps: Step 1: Crush and separate waste urea-formaldehyde resin-bonded engineered wood panels into recycled wood fibers; Step 2: Immerse the regenerated wood fiber in an organic acid buffer solution with a pH of 3.5 to 5.0 and treat it at 80 to 120°C for 15 to 30 minutes with a solid-liquid ratio of 1:8 to 1:12, so that the residual urea-formaldehyde resin fragments on the fiber surface partially depolymerize and generate amino groups in situ. Step 3: After washing and drying, apply polyphenol compound aqueous solution and trivalent metal salt aqueous solution in sequence; Step 4: After laying and molding, hot press at a temperature of 180 to 200°C, a pressure of 3.0 to 4.0 MPa, and a time of 5 to 7 minutes.
7. The preparation process according to claim 6, characterized in that: In step two, the organic acid buffer solution is a citric acid-sodium citrate buffer solution with a concentration of 0.02 to 0.10 mol / L, the treatment temperature is 90 to 105℃, and the treatment time is 18 to 25 min.
8. The preparation process according to claim 6, characterized in that: In step three, the polyphenol compound is tannic acid, the trivalent metal salt is ferric chloride hexahydrate, the mass fraction of the tannic acid aqueous solution is 15% to 25%, the mass fraction of the ferric chloride aqueous solution is 10% to 25%, the amount of tannic acid added is 5% to 8% of the dry fiber mass, and the molar ratio of trivalent iron ions to tannic acid is 0.8 to 1.
5.
9. The preparation process according to claim 6, characterized in that: In step four, the hot-pressing temperature is 185 to 195℃, the pressure is 3.2 to 3.8 MPa, the time is 5.5 to 6.5 min, and the target density of the board is 0.78 to 0.84 g / cm³. 3 .
10. The preparation process according to claim 6, characterized in that: It also includes a recycling step, in which waste boards are immersed in a citric acid aqueous solution with a pH of 3.0 to 3.5 and treated at 50 to 70°C for 2 to 4 hours to dissociate the coordination cross-linking network, separate and recycle the regenerated wood fibers, and then the recycled fibers are re-hot-pressed after being gently acid-hydrolyzed again and sizing with coordination adhesive to prepare new boards.
Citation Information
Patent Citations
Adhesive for artificial boards, and preparation method and application thereof
CN103740324A
Preparation method and application of urea-based phenolic resin based on urea-formaldehyde waste glue depolymerization
CN119331188A